2023
DOI: 10.1155/2023/6759698
|View full text |Cite
|
Sign up to set email alerts
|

AMMI and GGE Biplot Analyses for Mega Environment Identification and Selection of Some High-Yielding Cassava Genotypes for Multiple Environments

Abstract: Cassava (Manihot esculenta Crantz) is a staple food and generates income for smallholder farmers in southern Ethiopia. The performance of cassava genotypes varies in different growing environments; thus, the evaluation of genotypes tested in various environments plays an essential role in developing strategies to delineate environments, explore unstable genotypes in target environments, and identify stable genotypes for multiple environments. In this regard, there needs to be more information on the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…As a result, stable genotypes for a particular environment could be generated. This result is consistent with many studies that have shown a signi cant interaction between soybean genotypes and their environment [11,12]. Given that the genotypes exhibited different grain yield rankings across environments, the G*E interaction crossover (qualitative type) has strong implications for breeding for a particular adaptation [13] (Table 3).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As a result, stable genotypes for a particular environment could be generated. This result is consistent with many studies that have shown a signi cant interaction between soybean genotypes and their environment [11,12]. Given that the genotypes exhibited different grain yield rankings across environments, the G*E interaction crossover (qualitative type) has strong implications for breeding for a particular adaptation [13] (Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…However, the genotypes far from the biplot origin considered the best, those shown in Fig. 1, on the vertex are environment speci c [12]. The GGE biplot's average-environment coordination (AEC) is represented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Te feld experiment was conducted at Deneba and Wara trial sites for two consecutive main cropping seasons under rain-fed conditions during 2019 and 2020. Te geographical location of the Deneba trial site lies at 7 °21′N and 37 °38′E with an altitude of 1150 m above sea level [32]. During the experiment period, the average monthly rainfall in Deneba received 111 mm, with a mean monthly temperature of 26.5 °C (Figure 1).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Te Deneba site has nitosols, which is weathered red soil, and a detail description of the physical and chemical characteristics of the soil within the top 30 cm is presented in Table 1. Te Wara trial site is located at 7 °34′ N and 37 °44′ E with an altitude of 1550 m above sea level [32]. During the experiment period, the average monthly rainfall Wara received 138.5 mm with a mean monthly temperature 22.5 °C (Figure 2).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…This disproportionate genotype response is referred to as crossover GEI and same sign or near zero scores represent a non-crossover (quantitative) GEI or a proportionate genotype response [15,[26][27][28]. Genotypes and environments are displayed in the same scatter plot using the AMMI analysis biplot tool [6,12,22,29,40]. Moreover, various stability indices can be brought to use for evaluating the genotypes [4,21,33].…”
Section: Introductionmentioning
confidence: 99%